Effects of blowing ratio on the heat transfer coefficient distribution downstream of a single film cooling hole - Abu Talib, Abd Rahim; Jaafar, Abdul Aziz; Mokhtar, Ahmad Samsuri; Abd. Rahim, Irfan; Abdul Karim, M. S. (Federation of Engineering Institutions of Islamic Countries, 2006)
Detailed distributions of heat transfer coefficients downstream of a single film cooling hole were presented. The film cooling hole has an angle of inclination of 45° and a circular shape diameter of 10 mm. Tests were conducted in a purpose built heat transfer rig at the Department of Aerospace Engineering, UPM. The rig has been modified to conduct transient heat transfer testing using thermochromic liquid crystal technique. A single narrow-band liquid crystal was used to map the distribution of heat transfer coefficient downstream of a single film cooling hole at a blowing ratio ranging between 0.5-0.94. The detailed heat transfer coefficient distributions provide a clear understanding of free jet-mainstream flow interactions for different blowing ratio. Results shows that blowing ratio of 0.64 provides a better cooling protection compared to the other blowing ratios tested.